Ecomorphological Traits Determine Assemblage Pattern of Small Freshwater Fish in Smaller Lentic Aquatic Bodies - Roy, S.; Maiti, S. I.; Saikia, S. K.; Ray, S. (Journal of Scientific Research, 2020)
The present study investigated ecomorphological patterns of fish assemblage from freshwater ponds on two functional categories, i.e., foraging behavior and habitat preference. Nine ecomorphological indices were derived from eight morphometric variables and examined on 566 adult individuals belonging to 9 species, 7 families and 4 orders. Samples were collected during April 2016 to September 2017 from freshwater ponds in Birbhum, West Bengal. Mantel test was performed to investigate correlation between morphological, taxonomic, trophic and habitat guild matrices. The partial Mantel test was done to investigate the direct correlation between trophic and habitat guilds with morphology discounting the effect of taxonomic relatedness on species assemblage. The interspecific ecomorphological diversification pattern was analysed by HCPC method. At least three ecomorphological assemblages among these fish species with two significant principal axes of variations were observed. Ecomorphological attributes associated with mouth aspect ratio, compression index and relative body height were on PC1 axis, and relative length and height of head, relative area of eye were on PC 2 axis. Mantel and partial Mantel test showed significant correlation between morphology and trophic guild structure. Outcomes show that morphology is a good predictor of trophic structure of fish assemblage in studying convergent assemblage pattern irrespective of taxonomy.